RECEPTION OF HOAXES WITHIN MUSLIM COMMUNITY (UNDERSTANDING ATTITUDE AND BEHAVIOR TOWARDS MISLEADING INFORMATION IN THE AGE OF POST TRUTH POLITICS IN INDONESIA) - Sokowati, Muria Endah; Rochimah, Tri Hastuti Nur (International Journal of Psychosocial Rehabilitation, 2020)
This article introduces the massive distribution of hoaxes on 2014 presidential election and 2017 Jakarta Gubernatorial Election. It focuses on the attitude and behavior of Muslim communities towards hoaxes. The Muslim communities is chosen because both elections utilized issues related to religious sentiments, which contribute in increasing ideological polarization. This practice can certainly affect people with religious background. We argue that the Internet algorithms and selective exposure of information become the key factors in determining the process of viralization. Thus, the ideological orientation underlined both key factors will guide the religious users in constructing the fact. It truly exemplifies the practice of post truth politics in Indonesia. Since the sectarianism is significantly played by the political elites as contemporary electoral strategy to attract the voters; the Muslim communities, at the end are only played as the political object..